1996
DOI: 10.1212/wnl.47.5.1317
|View full text |Cite
|
Sign up to set email alerts
|

Selective staining of the cerebellar molecular layer by serum IgG in Miller-Fisher and related syndromes

Abstract: During 1 year, we used immunocytochemical staining of human cerebellum to screen 1,488 serums for IgG autoantibodies to Hu and Yo antigens. Three serums had none of the classically described patterns of IgG binding but instead, selectively stained the cerebellar molecular layer. Evaluation of clinical data showed that the patients had either typical Miller Fisher syndrome (MFS) or Guillain-Barré syndrome with ophthalmoplegia. Further analysis by ELISA, assay showed that all three serums had high titers of IgG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0
4

Year Published

1999
1999
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(38 citation statements)
references
References 8 publications
2
32
0
4
Order By: Relevance
“…Similarly, ataxia in our patients was attributed to be cerebellar in type and was noted without appreciable motor weakness or sensory deficits. In a study of immunocytochemical staining of human cerebellum by Kornberg et al [51], they found that only serums from the 3 patients with MFS or GBS with ophthalmoplegia selectively stained the cerebellar molecular layer. They concluded that the sepcificity of the serum IgG autoantibody binding to the cerebellar molecular layer may be related to the ataxia in those 3 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, ataxia in our patients was attributed to be cerebellar in type and was noted without appreciable motor weakness or sensory deficits. In a study of immunocytochemical staining of human cerebellum by Kornberg et al [51], they found that only serums from the 3 patients with MFS or GBS with ophthalmoplegia selectively stained the cerebellar molecular layer. They concluded that the sepcificity of the serum IgG autoantibody binding to the cerebellar molecular layer may be related to the ataxia in those 3 patients.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that the ataxia could result from mismatch of input of joint receptors and proprioception to the CNS [10]. Other evidence supporting a central origin of ataxia in MFS includes the presence of cerebellar neuronal antibodies in some patients [7] and the finding of spinocerebellar tracts enhancing lesions in one case [13]. Bickerstaff [1] considers the lesion site in the MFS to be the brainstem.…”
mentioning
confidence: 99%
“…Greater amounts of ganglioside GQ1b have been found in cranial nerves III, IV and VI 12 and these nerves were enhanced by gadolinium on MRI in patients with MFS 13 . A selective staining of the cerebellar molecular layer by serum IgG antiGQ1b has also been observed 14 . Although the presence of this antibody could be a secondary phenomenon due to destruction of neurons, some evidence points to a pathogenetic role, with blocking effects on the neuromuscular transmission 15 .…”
Section: Fig 2 Right Eye Campimetry Performed At the Forth (A) And Tmentioning
confidence: 84%